The Knowledge Level of IKOR UNNES Students on the Effect of Neurobic Exercise on Cognitive Function Improvement - Alfauzani, Muhammad Rifqi; Setiowati, Anies (Media Ilmu Keolahragaan Indonesia, 2024)
Neurobic Exercise is a training method that combines both physical and sensory faculty such as hearing, cognition and memory (Dighe, et al., 2020). Neurobic exercises provides stimulus that can improve cognitive abilities such as alertness, concentration, speed, perception, learning, memory, problem solving and creativity. Furthermore, to gain more optimal result in some exercise, we need to first understand how this kind of exercises method works. Therefore, this study aims to determine the level of knowledge of UNNES Sports Science students regarding the effect of neurobic training on improving cognitive function. This research is quantitative descriptive research with a survey method. This research uses questionnaire with 3 indicators with a total of 30 question items. A total of 56 samples were taken using purposive sampling method. Quantitative descriptive analysis technique was used to analyze the data sample. The results showed there were 45 samples having a good level of knowledge whereas other 11 were on moderate level of knowledge. The average score obtained was 22.9 with a standard deviation of 2.47. The highest score obtained was 28 while the lowest score was 17. The conclusion of this research is that UNNES Sports Science students have a good level of knowledge about neurobic exercise and its effect on improving cognitive function.